A regional geography of gentrification, displacement, and the suburbanisation of poverty: Towards an extended research agenda. Issue 3 (3rd May 2021) - Hochstenbach, Cody; Musterd, Sako
Abstract : Gentrification is now a common feature of contemporary cities. The process has extended its spatial reach from urban cores into neighbourhoods previously deemed unlikely to gentrify. More recently, scholars have identified an intensifying suburbanisation of poverty reshaping socio‐spatial inequalities. In this paper we argue that it is increasingly urgent to integrate analyses of gentrification with those on the suburbanisation of poverty. The two processes are fundamentally related through the displacement and exclusion of disadvantaged populations. Drawing on Dutch full‐population register data for the 2005–2015 period, we empirically illustrate the existence of suburbanising poverty alongside urban gentrification in the urban regions of Amsterdam and Utrecht. We further show these are far from uniform processes, eschewing urban–suburban dichotomies. In addition, we find regional differences in the intensity and spatial reach of both gentrification and poverty suburbanisation. Spatial trends are more pronounced in the Amsterdam region, where low‐income households are pushed to the furthest parts of the region. By way of conclusion, we outline an agenda for future research. Abstract : In this paper we argue that it is increasingly urgent to integrate analyses of gentrification with those on the suburbanisation of poverty. The two processes are fundamentally related through the displacement and exclusion of disadvantaged populations. We empirically illustrate our arguments drawing on the cases of Amsterdam and Utrecht (the Netherlands), and outline an agenda for future research.